Phyllodes tumour of the prostate posing diagnostic and therapeutic dilemmas. (2nd December 2010) - Maudlin, Lucy; Ball, Richard Y; Irving, Stuart; Preston, Peter; Chitale, Sudhanshu
Abstract : A rare case of phyllodes tumour of the prostate of which less than 100 cases have been reported in the literature. It has an unclear clinical course and uncertain management options. In an inoperable case such as this, the authors discuss the difficulties faced with its management and the limited, possibly palliative role, of hormonal treatment using luteinising hormone-releasing hormone analogue in managing it over a medium term.